Thermoplastic resin composition for electromagnetic wave absorber and molded body

A thermoplastic resin composition with optimized olefin and styrene elastomers, carbon nanotubes, and carbon black addresses the need for improved electromagnetic wave absorption, flexibility, and heat resistance in automotive applications, enhancing millimeter wave radar device performance.

JP2025012994AActive Publication Date: 2025-01-24TOYO INK MFG CO LTD +3
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023116232
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-24
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

Existing electromagnetic wave absorbers, particularly those used in automotive applications, require improved electromagnetic wave absorption, flexibility, and heat resistance to effectively shield millimeter wave radar devices from interference and maintain detection accuracy.

Method used

A thermoplastic resin composition comprising specific ratios of olefin elastomers, styrene elastomers, carbon nanotubes, and carbon black, which are blended and molded to create a material with enhanced electromagnetic wave absorption, flexibility, and heat resistance.

Benefits of technology

The composition achieves good electromagnetic wave absorption, flexibility, and heat resistance, making it suitable for millimeter wave radar devices, particularly in automotive applications, by optimizing the conductive filler distribution and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012994000009
    Figure 2025012994000009
  • Figure 2025012994000001
    Figure 2025012994000001
  • Figure 2025012994000002
    Figure 2025012994000002
Patent Text Reader

Abstract

To provide a thermoplastic resin composition for an electromagnetic wave absorber from which a molded body having good electromagnetic wave absorption property and flexibility, and excellent heat resistance can be obtained.SOLUTION: A thermoplastic resin composition for an electromagnetic wave absorber contains 50 to 80 mass% of an olefinic elastomer (A) having a tensile breaking elongation rate measured according to ISO37 of 400 to 700%, 15 to 35 mass% of an elastomer (B) containing at least one kind selected from the group consisting of a styrenic elastomer (B1) and an olefinic elastomer (B2) having tensile breaking elongation rate measured according to ISO37 of 800% or more, 0.5 to 5 mass% of a carbon nanotube (C), and 3 to 15 mass% of a carbon black (D).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] An embodiment of the present invention relates to a thermoplastic resin composition for an electromagnetic wave absorber and a molded article thereof. [Background technology]

[0002] Since plastics are easy to mold, they are used in a wide range of fields, such as electrical equipment parts, electronic equipment parts, automobile parts, medical parts, food containers, etc., and coloring of plastic molded products is widely carried out to enhance their decorativeness and to impart functionality. Particularly in the automobile field, colored molded products intended for electromagnetic wave absorption purposes are in circulation as products that have been given functionality.

[0003] Electromagnetic waves are emitted from communication devices such as radios, televisions, and wireless communication devices, but also from electronic devices such as mobile phones and personal computers, which have rapidly increased in number due to recent advances in information technology. Conventionally, one method for preventing malfunctions of electronic devices and communication devices due to electromagnetic waves has been to install electromagnetic wave absorbers near or far from the electromagnetic wave generating part, which efficiently absorb the electromagnetic waves and convert the absorbed electromagnetic waves into thermal energy.

[0004] An example of an electromagnetic wave absorber installed far away from the electromagnetic wave generating point is the use in an electronic toll collection system (ETC) on expressways. ETC is a system that exchanges billing information, etc., using microwaves with a frequency of 5.8 GHz between a roadside unit antenna installed at a toll booth and an on-board unit antenna when a car passes through a toll booth exit on an expressway. In toll booths where this ETC system has been introduced, microwaves emitted from the antenna are reflected by the toll booth roof, etc., causing unnecessary electromagnetic waves to leak from adjacent ETC lanes, which can cause communication abnormalities. Therefore, electromagnetic wave absorbers are installed on the toll booth roof or between the ETC lanes to suppress communication abnormalities.

[0005] In recent years, millimeter-wave radars have been used in the automotive field for the purpose of automatic vehicle driving and collision prevention, and in many cases, millimeter-wave radar devices are installed inside automobiles. Millimeter waves are electromagnetic waves with wavelengths of 1 to 10 mm and frequencies of 30 to 300 GHz, and are currently used in vehicle-mounted radars, full-body scanners that see through clothing as a crime prevention check at airports, and video transmission from surveillance cameras on platforms during one-man train operation. Millimeter-wave radar devices are devices that can recognize obstacles by emitting millimeter waves and receiving the waves that bounce back. They are currently used in automatic driving technologies for automobiles and other vehicles because of their long detectable distances and their resistance to obstruction by sunlight, rain, and fog. In the case of automobile sensors, millimeter-wave radar devices can detect the relative distance and relative speed of obstacles by transmitting and receiving millimeter waves from an antenna.

[0006] The transmitting and receiving antennas of these millimeter wave radar devices may receive reflections from the road surface and other objects other than the target obstacle, which may reduce the detection accuracy of the device. To solve this problem, millimeter wave radar devices are provided with an electromagnetic wave absorber between the antenna and the control circuit as a shielding member that blocks electromagnetic waves.

[0007] Known millimeter wave band electromagnetic wave absorbing materials that make up such electromagnetic wave absorbers include carbon-based, metal-carbon-based, and magnetic-based materials. For example, carbon-based electromagnetic wave absorbers containing carbon nanotubes (CNTs) are used because of their high electrical conductivity and relatively light weight (Patent Document 1). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Special Publication No. 2017-512847 Summary of the Invention [Problem to be solved by the invention]

[0009] Patent Document 1 discloses a method of adding carbon nanotubes instead of conductive carbon black to an electromagnetic wave absorber in order to improve conductivity while reducing the amount of conductive filler added, and according to Patent Document 1, a composite material containing carbon nanotubes has excellent conductivity and improved mechanical properties. However, further improvements in electromagnetic wave absorbers are desired for use in recent automobile fields and the like.

[0010] Therefore, some embodiments of the present invention have an object to provide a thermoplastic resin composition for a radio wave absorber that can provide a radio wave absorber having good electromagnetic wave absorbency and flexibility, and further having excellent heat resistance. Also, some embodiments of the present invention have an object to provide a molded article having good electromagnetic wave absorbency and flexibility, and further having excellent heat resistance. [Means for solving the problem]

[0011] As a result of extensive investigations, the present inventors have found that the problems of the present invention can be solved in the following aspect, and have thus completed the present invention.

[0012] The present invention includes the following embodiments, but is not limited to the following embodiments. (1) A thermoplastic resin composition for an electromagnetic wave absorber, comprising: 50 to 80 mass% of an olefin-based elastomer (A) having a tensile elongation at break of 400 to 700% measured in accordance with ISO 37:2017; 15 to 35 mass% of an elastomer (B) including at least one selected from the group consisting of a styrene-based elastomer (B1) and an olefin-based elastomer (B2) having a tensile elongation at break of 800% or more measured in accordance with ISO 37:2017; 0.5 to 5 mass% of carbon nanotubes (C); and 3 to 15 mass% of carbon black (D). (2) The thermoplastic resin composition for an electromagnetic wave absorber according to the above (1), wherein the elastomer (B) comprises the styrene-based elastomer (B1), and the styrene-based elastomer (B1) comprises at least one selected from the group consisting of styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-ethylene-propylene block copolymer (SEP), styrene-ethylene-propylene-styrene block copolymer (SEPS), and styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS). (3) The thermoplastic resin composition for an electromagnetic wave absorber according to the above (1) or (2), wherein the elastomer (B) contains the styrene-based elastomer (B1), and the content of the styrene structure in the styrene-based elastomer (B1) is 15 to 35 mass%. (4) The thermoplastic resin composition for an electromagnetic wave absorber according to any one of the above (1) to (3), wherein the elastomer (B) comprises the olefin-based elastomer (B2), and the olefin-based elastomer (B2) comprises an ethylene-α-olefin copolymer. (5) A molded article obtained by molding the thermoplastic resin composition for an electromagnetic wave absorber according to any one of (1) to (4) above. Effect of the Invention

[0013] According to some embodiments of the present invention, the thermoplastic resin composition for a radio wave absorber can produce a radio wave absorber having good electromagnetic wave absorbency and flexibility, and further having excellent heat resistance. According to some embodiments of the present invention, the molded article has good electromagnetic wave absorbency and flexibility, and further has excellent heat resistance. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a conceptual diagram showing how to measure the transmission loss and return loss using a millimeter wave transmitting device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in detail below. In this specification, a numerical range specified using "to" is intended to include the numerical values ​​before and after "to" as the lower and upper limit values. In addition, "olefin-based elastomer (A) having a tensile elongation at break of 400 to 700% measured in accordance with ISO 37:2017" may be referred to as "olefin-based elastomer (A)", olefin-based elastomer (B2) having a tensile elongation at break of 800% or more measured in accordance with ISO 37:2017 may be referred to as "olefin-based elastomer (B2)", "elastomer (B) comprising at least one selected from the group consisting of styrene-based elastomer (B1) and olefin-based elastomer (B2)" may be referred to as "elastomer (B)", a thermoplastic resin composition for electromagnetic wave absorber may be referred to as "thermoplastic resin composition", and "carbon nanotubes" may be referred to as "CNT". In addition, unless otherwise noted, the various components appearing in this specification may each be used independently as a single type, or as a combination of two or more types. The numerical values ​​specified in this specification are values ​​determined by the methods disclosed in the embodiments or examples.

[0016] <Thermoplastic resin composition for electromagnetic wave absorber> According to an embodiment of the present invention, the thermoplastic resin composition for an electromagnetic wave absorber contains 50 to 80 mass% of an olefin-based elastomer (A) having a tensile elongation at break of 400 to 700% measured in accordance with ISO 37:2017 (hereinafter referred to as "ISO37"), 15 to 35 mass% of an elastomer (B) including at least one selected from the group consisting of a styrene-based elastomer (B1) and an olefin-based elastomer (B2) having a tensile elongation at break of 800% or more measured in accordance with ISO37, 0.5 to 5 mass% of carbon nanotubes (C), and 3 to 15 mass% of carbon black (D).

[0017] [Olefin elastomer (A)] The olefin-based elastomer (A) has a tensile elongation at break of 400 to 700% measured according to ISO37. If the tensile elongation at break is 400% or more, the efficiency of radio wave transmission between conductive fillers such as carbon nanotubes and carbon black is improved, which is preferable in terms of electromagnetic wave absorption and flexibility. The tensile elongation at break is preferably 500% or more, more preferably 550% or more, and even more preferably 600% or more. If the tensile elongation at break is 700% or less, it is preferable in terms of heat resistance. The tensile elongation at break is preferably 680% or less, and more preferably 650% or less.

[0018] In an embodiment of the present invention, the tensile elongation at break is a value obtained by measurement in accordance with ISO 37. Specifically, a test piece (a dumbbell-shaped No. 3 test piece prepared in accordance with JIS K 6251:2017) is measured using a material testing machine (for example, "3367" manufactured by Instron Corporation) in an atmosphere at a temperature of 23°C and at a tensile speed of 500 mm / min.

[0019] The melt mass flow rate (MFR) of the olefin-based elastomer (A) is, for example, 0.1 to 50 g / 10 min. The MFR is preferably 5 g / 10 min or more, more preferably 15 g / 10 min or more, and even more preferably 20 g / 10 min or more. In particular, when the MFR is 5 g / 10 min or more, the conductive filler can be uniformly dispersed in the molded product, which is preferable in terms of electromagnetic wave absorption and moldability. The MFR is preferably 45 g / 10 min or less, more preferably 40 g / 10 min or less, and even more preferably 30 g / 10 min or less. When the MFR is 50 g / 10 min or less, it is preferable in terms of heat resistance.

[0020] In an embodiment of the present invention, MFR is a value of melt mass flow rate measured in accordance with JIS K 7210: 1999. Specifically, the measurement is performed using a melt flow rate measuring device (for example, "Melt Indexer" manufactured by Toyo Seiki Seisakusho) under conditions of a temperature of 230°C and a load of 2.16 kgf.

[0021] The olefin elastomer (A) is preferably a mixed material in which an elastic rubber component is dispersed in polyolefin, which is a molecular restraining component that prevents plastic deformation. The rubber component may be an uncrosslinked rubber component, a partially crosslinked rubber component, or a completely crosslinked rubber component. Crosslinking may be, for example, dynamic crosslinking carried out during mixing and kneading of the polyolefin and the rubber component. In the mixed material, a part of the polyolefin and the rubber component may be graft polymerized.

[0022] Examples of the polyolefin, which is a molecular constraint component, include crystalline polyolefins such as polyethylene, polypropylene, etc. Examples of the rubber component include ethylene propylene rubbers such as ethylene-propylene copolymer (EPM), ethylene-butylene copolymer (EBM), and ethylene-propylene-diene terpolymer (EPDM), and acrylonitrile butadiene rubber (NBR).

[0023] From the viewpoint of heat resistance, the olefin-based elastomer (A) is preferably a dynamically crosslinked olefin-based thermoplastic elastomer, and is preferably a dynamically crosslinked elastomer using crystalline polypropylene as a molecular restraining component and ethylene-propylene-diene terpolymer (EPDM) as a rubber component.

[0024] Examples of commercially available olefin-based elastomers (A) include Milastomer 9070NS, Milastomer L900NS, and Milastomer A970B manufactured by Mitsui Chemicals, Inc.; Actima-GA-1075N and Actima-LVG9541S manufactured by Riken Technos Corporation; Santoprene 201-87 and Santoprene 203-40 manufactured by Exxon Mobil Corporation; Sarlink 4190, Sarlink 3190, and Sarlink 4155 manufactured by Toyobo Co., Ltd.; and EXCELINK 1300B, EXCELINK 1404B, and EXCELINK 1309B manufactured by JSR Corporation.

[0025] The content of the olefin elastomer (A) is 50 to 80% by mass based on the mass of the thermoplastic resin composition. A content of 50% by mass or more is preferable in terms of the manufacturability of the thermoplastic resin composition and the molded article. The content is preferably 55% by mass or more, more preferably 60% by mass or more, and even more preferably 65% ​​by mass or more. A content of 80% by mass or less is preferable in terms of electromagnetic wave absorbency. The content is preferably 75% by mass or less, more preferably 70% by mass or less, and even more preferably 70% by mass or less.

[0026] [Elastomer (B)] The thermoplastic resin composition contains at least one elastomer (B) selected from the group consisting of a styrene-based elastomer (B1) and an olefin-based elastomer (B2). The elastomer (B) may be a styrene-based elastomer (B1), an olefin-based elastomer (B2), or both the styrene-based elastomer (B1) and the olefin-based elastomer (B2).

[0027] (Styrene-based elastomer (B1)) The styrene-based elastomer (B1) may be a block copolymer of styrene and at least one selected from the group consisting of α-olefins and diolefins. The styrene may be substituted or unsubstituted, and is preferably unsubstituted. Examples of α-olefins are as described below. Examples of diolefins (dienes) include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, and the like. The styrene-based elastomer (B1) may be a styrene-based thermoplastic elastomer or a hydrogenated styrene-based thermoplastic elastomer.

[0028] In the styrene elastomer (B1), the content of the styrene structure is, for example, 15 to 35% by mass based on the mass of the styrene elastomer (B1). When the content of the styrene structure is 15% by mass or more, the ratio of the styrene structure, which is a hard segment, is high, which is preferable in terms of heat resistance. The content of the styrene structure is preferably 18% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. When the content of the styrene structure is 35% by mass or less, the ratio of the α-olefin structure, which is a soft segment, is high, which is preferable in terms of flexibility. In addition, the compatibility with the olefin elastomer (A) is improved, which is preferable in terms of electromagnetic wave absorption. The content of the styrene structure is preferably 34% by mass or less, more preferably 32% by mass or less, and even more preferably 30% by mass or less.

[0029] The solution viscosity of the styrene-based elastomer (B1) is, for example, 30 mPa·s or more, preferably 50 mPa·s or more, more preferably 100 mPa·s or more, and even more preferably 200 mPa·s or more. A solution viscosity of 30 mPa·s or more is preferable in terms of heat resistance. There is no particular upper limit to the solution viscosity, but from the viewpoint of compatibility with the olefin-based elastomer (A), it may be 1,000 mPa·s or less or 500 mPa·s or less.

[0030] In an embodiment of the present invention, the solution viscosity of the styrene-based elastomer (B1) is a value measured using a toluene solution obtained by dissolving the styrene-based elastomer (B1) in a toluene solvent to a concentration of 5% by mass, using a B-type viscometer in an atmosphere at a temperature of 30° C. As the B-type viscometer, for example, "VISCOMETER TVB-10" manufactured by Toki Sangyo Co., Ltd. can be used.

[0031] From the viewpoint of heat resistance, the styrene-based elastomer (B1) is preferably a block copolymer having a styrene structure as a hard segment and a hydrogenated polydiene structure as a soft segment.

[0032] Examples of the styrene-based elastomer (B1) include styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-ethylene-propylene block copolymer (SEP), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-butadiene-styrene block copolymer (SBS), styrene-butadiene-styrene-butadiene block copolymer (SBSB), styrene-butadiene-butylene-styrene block copolymer (SBBS), etc. The styrene-based elastomer (B1) preferably contains at least one selected from the group consisting of styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-ethylene-propylene block copolymer (SEP), styrene-ethylene-propylene-styrene block copolymer (SEPS), and styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS). From the viewpoints of heat resistance, electromagnetic wave absorption, and moldability, the thermoplastic resin composition more preferably contains at least one selected from the group consisting of styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), and styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), and further preferably contains at least one selected from the group consisting of styrene-ethylene-butylene-styrene block copolymer (SEBS) and styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS).

[0033] Examples of commercially available styrene-based elastomers (B1) include Septon 4077, Septon 4055, Septon 8006, Septon 4044, and Septon 2005 manufactured by Kuraray Co., Ltd.; Tuftec H1221, Tuftec H1041, and Tuftec H1051 manufactured by Asahi Kasei Chemicals Corporation; and Kraton G1643M, Kraton G1645M, and Kraton G1652H manufactured by Kraton Polymers.

[0034] The content of the styrene-based elastomer (B1) is 15 to 35% by mass based on the mass of the thermoplastic resin composition. A content of 15% by mass or more is preferable in terms of flexibility. The content is preferably 16% by mass or more, more preferably 18% by mass or more, and even more preferably 20% by mass or more. A content of 35% by mass or less is preferable in terms of heat resistance and electromagnetic wave absorption. The content is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 23% by mass or less. When the thermoplastic resin composition contains the styrene-based elastomer (B1), heat resistance is improved.

[0035] (Olefin elastomer (B2)) The olefin elastomer (B2) has a tensile elongation at break of 800% or more as measured according to ISO 37. A tensile elongation at break of 800% or more is preferable in terms of flexibility and electromagnetic wave absorption. The tensile elongation at break is preferably 1,000% or more. There is no particular upper limit to the tensile elongation at break, but it may be 1,500% or less.

[0036] The olefin elastomer (B2) is preferably an uncrosslinked or partially crosslinked elastomer, more preferably an uncrosslinked elastomer, and may be, for example, an olefin homopolymer or an olefin copolymer. The olefin copolymer may be, for example, a copolymer of at least two α-olefins, a copolymer of ethylene and an α-olefin, or a copolymer of ethylene and at least one α-olefin having 3 or more carbon atoms. The olefin elastomer (B2) may be a copolymer of an olefin and maleic acid, a copolymer of an olefin and a (meth)acrylic acid ester, or the like.

[0037] Examples of α-olefins include ethylene, propylene, 1-butene, 2-methyl-1-propene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, dimethyl 1-pentene, ethyl-1-pentene, trimethyl-1-butene, methylethyl-1-butene, 1-octene, methyl-1-pentene, ethyl-1-hexene, dimethyl-1-hexene, propyl-1-heptene, methylethyl-1-heptene, trimethyl-1-pentene, propyl-1-pentene, diethyl-1-butene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, and the like.

[0038] The α-olefin preferably contains 1-butene, which is commercially available and has excellent flexibility.

[0039] The melt mass flow rate (MFR) of the olefin elastomer (B2) is, for example, 0.1 to 50 g / 10 min. The MFR is preferably 3 g / 10 min or more, more preferably 5 g / 10 min or more, and may be 20 g / 10 min or more. In particular, an MFR of 3 g / 10 min or more is preferable in terms of electromagnetic wave absorption. Moreover, the MFR is preferably 20 g / 10 min or less, more preferably 10 g / 10 min or less. In particular, an MFR of 20 g / 10 min or less is preferable in terms of moldability and heat resistance.

[0040] Examples of the olefin elastomer (B2) include ethylene-propylene copolymer, ethylene-butene-1 copolymer, ethylene-hexene-1 copolymer, ethylene-octene-1 copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylate copolymer, propylene-ethylene-1-butene copolymer, ethylene-1-butene copolymer, polybutene, polyisobutylene, or maleic acid modified products thereof, etc. As the olefin elastomer (B2), propylene-ethylene-1-butene copolymer is preferred because it is easily available.

[0041] Commercially available olefin-based elastomers (B2) include, for example, TAFMER PN-3560, MH-5010, PN-20300, MA9015, and XM-7090 manufactured by Mitsui Chemicals; and ENGAGE 8130, ENGAGE 8200, and ENGAGE 8400 manufactured by Dow Chemical.

[0042] The content of the olefin elastomer (B2) is 15 to 35% by mass based on the mass of the thermoplastic resin composition. A content of 15% by mass or more is preferable in terms of flexibility. The content is preferably 16% by mass or more, more preferably 18% by mass or more, and even more preferably 20% by mass or more. A content of 35% by mass or less is preferable in terms of heat resistance and electromagnetic wave absorption. The content is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 23% by mass or less.

[0043] The styrene-based elastomer (B1) and the olefin-based elastomer (B2) can be used in combination. When used in combination, in terms of flexibility and heat resistance, it is preferable that the amount of the olefin-based elastomer (B2) is less than 100% by mass, and more preferably 50% by mass or less, per 100% by mass of the styrene-based elastomer (B1).

[0044] The content of the elastomer (B) is 15 to 35% by mass based on the mass of the thermoplastic resin composition. A content of 15% by mass or more is preferable in terms of flexibility. The content is preferably 16% by mass or more, more preferably 18% by mass or more, and even more preferably 20% by mass or more. A content of 35% by mass or less is preferable in terms of heat resistance and electromagnetic wave absorption. The content is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 23% by mass or less. When the elastomer (B) contains a styrene-based elastomer (B1) and an olefin-based elastomer (B2), the "content of the elastomer (B)" refers to the total content of both when the elastomer (B) contains only one of them, and refers to the content of the one when the elastomer (B) contains only one of them.

[0045] [Carbon nanotubes (C)] The carbon nanotubes (C) may be single-walled carbon nanotubes, multi-walled carbon nanotubes wound with two or more layers, or a mixture of these, but are preferably multi-walled carbon nanotubes in terms of cost and strength. Also, carbon nanotubes whose sidewalls have an amorphous structure instead of a graphite structure may be used.

[0046] Carbon nanotubes (C) can generally be produced by laser ablation, arc discharge, chemical vapor deposition (CVD), combustion, etc., but any method may be used. In particular, the CVD method is a method for inexpensively and mass-producing carbon nanotubes by contacting fine catalyst particles, which are formed by supporting a metal catalyst such as iron or nickel on a support such as silica, alumina, magnesium oxide, titanium oxide, silicate, diatomaceous earth, alumina silica, silica titania, or zeolite, with a carbon-containing gas as a raw material, at a high temperature of usually 400 to 1000°C, and is also preferable as the carbon nanotubes used in the embodiment of the present invention.

[0047] The carbon nanotubes (C) preferably have an average diameter of 1 to 30 nm, more preferably 2 to 25 nm, and even more preferably 5 to 20 nm, as determined by a scanning electron microscope. When the average diameter is within this range, the carbon nanotubes are highly dispersible in the thermoplastic resin composition, and the resulting molded article has excellent electromagnetic wave absorption performance.

[0048] The average diameter of carbon nanotubes is determined using a scanning electron microscope (e.g., JSM-6700M, manufactured by JEOL). The conditions are as follows: carbon nanotubes are observed at an accelerating voltage of 5 kV, and an image is taken at 50,000 times magnification (1024 × 1280 pixels), and then the short axis length of each of 20 random carbon nanotubes in the taken image is measured, and the number average of the short axis lengths is calculated as the average diameter of the carbon nanotubes.

[0049] Examples of commercially available carbon nanotubes include CM-130 and CM-250 manufactured by Hanhwa Chemical Industries, Ltd.; SNW210 manufactured by SouthWest NanoTechnologies, Inc.; Flotube7000 and Flotube3100 manufactured by CNano Corporation; and Graphistrength C100 manufactured by Arkema.

[0050] The content of carbon nanotubes (C) is 0.5 to 5% by mass based on the mass of the thermoplastic resin composition. If the content is 0.5% by mass or more, radio wave transmission within the molded body becomes smooth, which is preferable in terms of electromagnetic wave absorption (particularly transmission loss) and also in terms of heat resistance. If the content is 5% by mass or less, radio waves are easily taken in by the surface of the molded body, which is preferable in terms of electromagnetic wave absorption (particularly reflection loss) and also in terms of flexibility. The content is preferably 1% by mass or more, more preferably 1.5% by mass or more. The content is preferably 4% by mass or less, more preferably 3% by mass or less.

[0051] [Carbon Black (D)] As the carbon black (D), various types of carbon black can be used alone or in combination, such as furnace black produced by continuously pyrolyzing a gaseous or liquid raw material in a reactor, ketjen black, particularly made from ethylene heavy oil, channel black, which is produced by burning a raw material gas and quenching it by applying the flame to the bottom surface of a channel steel, thermal black, which is obtained by periodically repeating combustion and pyrolysis of a gas as a raw material, and acetylene black, particularly made from acetylene gas as a raw material. Carbon black that has been subjected to a commonly used oxidation treatment and hollow carbon can also be used.

[0052] The carbon black (D) preferably has an average primary particle size of 20 to 60 nm, more preferably 30 to 50 nm, and even more preferably 35 to 45 nm, as determined by a scanning electron microscope. When the average primary particle size is within this range, the carbon nanotubes (C) incorporated inside the molded product after injection molding or extrusion molding can effectively form conductive paths with each other, enabling the molded product to exhibit stable high electrical conductivity and electromagnetic wave absorption.

[0053] Specifically, the average primary particle size of carbon black is determined, for example, using a scanning electron microscope (JSM-6700M, manufactured by JEOL Ltd.) The conditions are as follows: carbon black is observed at an accelerating voltage of 5 kV, an image is taken at 50,000 times magnification (1024 × 1280 pixels), and then the particle size of each of 20 random carbon black particles in the taken image is measured, and the number average value is calculated as the average primary particle size of carbon black.

[0054] Examples of commercially available carbon black include furnace blacks manufactured by Shin-Nichika Carbon Co., Ltd., such as Niteron #10, #200, and #300; furnace blacks manufactured by Tokai Carbon Co., Ltd., such as Toka Black #4300, #4400, #4500, and #5500; furnace blacks manufactured by Degussa Corporation, such as Printex L; Raven 7000, 5750, 5250, 5000ULTRAIII, 5000ULTRA, Conductex SC ULTRA, 975ULTRA, PUER Columbian furnace blacks such as BLACK100, 115, and 205; Mitsubishi Chemical furnace blacks such as #30B, #45, #2350, #2400B, #2600B, #30050B, #3030B, #3230B, #3350B, #3400B, and #5400B; Cabot furnace blacks such as MONARCH1400, 1300, 900, VulcanXC-72R, and BlackPearls2000; Ensaco250G Examples of suitable black blacks include, but are not limited to, furnace blacks manufactured by Imerys, such as Ensaco 260G, Ensaco 350G, and Super P-Li; ketjen blacks manufactured by Akzo, such as Ketjen Black EC-300J and EC-600JD; acetylene blacks manufactured by Denki Kagaku Kogyo, such as Denka Black HS-100 and FX-35; and ketjen blacks manufactured by Lion Specialty Chemicals, such as Carbon ECP and Carbon ECP600JD.

[0055] The content of carbon black (D) is 3 to 15% by mass based on the mass of the thermoplastic resin composition. When the content is 3% by mass or more, radio wave transmission within the molded body becomes smooth, which is preferable in terms of electromagnetic wave absorption (particularly transmission loss) and also in terms of heat resistance. When the content is 15% by mass or less, radio waves are easily taken in by the surface of the molded body, which is preferable in terms of electromagnetic wave absorption (particularly reflection loss) and also in terms of flexibility. The content is preferably 5% by mass or more, more preferably 7% by mass or more. The content is preferably 12% by mass or less, more preferably 10% by mass or less.

[0056] The content ratio of carbon nanotubes (C) to carbon black (D) is preferably carbon nanotubes (C) / carbon black (D)=1 / 2 to 1 / 7, more preferably 1 / 3 to 1 / 5. Within the above range, it is possible to achieve both reflection loss and transmission loss in electromagnetic wave absorption.

[0057] [Other optional ingredients] The thermoplastic resin composition can contain other optional components, such as a polymer other than the olefin-based polymer (A) and the elastomer (B), an electromagnetic wave absorbing material, a weather stabilizer, an antistatic agent, a dye, a pigment, a coupling agent, a crystal nucleating agent, and a resin filler, as necessary.

[0058] The thermoplastic resin composition preferably does not contain a volatile component. In 100% by mass of the thermoplastic resin composition, the amount of volatile components such as solvents and low molecular weight components is preferably 5% by mass or less, and more preferably 1% by mass or less.

[0059] [Method of producing thermoplastic resin composition] The method for producing the thermoplastic resin composition is not particularly limited. For example, the olefin elastomer (A), the elastomer (B), the carbon nanotube (C), the carbon black (D), and further additives, etc., are mixed in a Henschel mixer, a tumbler, a disperser, etc., and mixed or melt-kneaded in a batch kneader such as a kneader, a roll mill, a super mixer, a Henschel mixer, a Schuggie mixer, a vertical granulator, a high-speed mixer, a Furmatrix, a ball mill, a steel mill, a sand mill, a vibration mill, an attritor, or a Banbury mixer, a twin-screw extruder, a single-screw extruder, or a rotor-type twin-screw kneader, etc., to obtain a resin composition in the form of pellets, powder, granules, beads, etc. It is preferable to use a twin-screw extruder for melt-kneading.

[0060] <Molded body> According to an embodiment of the present invention, a molded article is formed using the thermoplastic resin composition of the above embodiment and used as an electromagnetic wave absorber. The molded article can be obtained by melting the thermoplastic resin composition in a molding machine, forming the shape of the molded article, and cooling it. The temperature of the molding machine is not a problem as long as it is a temperature at which the olefin-based elastomer (A) and the elastomer (B) soften, but is preferably a temperature 30°C or higher than the softening points of both. It is preferable that the molded article can be in the shape of a plate, rod, fiber, tube, pipe, bottle, film, etc.

[0061] Examples of the molding method that can be used include extrusion molding, injection molding, blow molding, compression molding, transfer molding, film molding such as T-die molding and inflation molding, calendar molding, and fiber spinning.

[0062] The electromagnetic wave absorber converts the energy of the incident electromagnetic wave into heat energy inside the absorber and absorbs it. Unlike an electromagnetic wave shielding material, the electromagnetic wave absorber aims to absorb the radio wave inside the molded body without reflecting the radio wave on the surface of the molded body. The electromagnetic wave absorber is used in the automobile field such as an automatic toll collection system (ETC) on a highway, an in-vehicle radar, a full-body scanner that sees through clothes as a crime prevention check at an airport, a millimeter wave radar device used for transmitting images from a surveillance camera on a platform during one-man operation of a train, and a radar false image prevention of a ship mast. In particular, the molded body formed by the thermoplastic resin composition according to the embodiment of the present invention is excellent in electromagnetic wave absorption performance in the millimeter wave band of 60 to 90 GHz, and therefore can be suitably used for a millimeter wave radar device. EXAMPLES

[0063] The present invention will be described in more detail below with reference to examples, but the following examples do not limit the present invention in any way. In the examples, "parts" means "parts by mass" and "%" means "% by mass." The blending amounts in the tables are in % by mass, and blank spaces in the tables indicate that no blending was performed.

[0064] The tensile elongation at break and MFR of the olefin-based elastomer (A) and the olefin-based elastomer (B2), the solution viscosity of the styrene-based elastomer (B1), the average diameter of the carbon nanotubes (C), and the average primary particle size of the carbon black (D) were measured by the following methods.

[0065] (Tensile elongation at break of olefin-based polymer (A) and olefin-based elastomer (B2)) The tensile elongation at break was measured in accordance with ISO 37. Specifically, the test pieces (dumbbell-shaped No. 3 test pieces prepared according to JIS K 6251:2017) made using the elastomer were measured using an Instron material testing machine "3367" at an atmosphere temperature of 23°C and a tensile speed of 500 mm / min.

[0066] (MFR (Melt Mass Flow Rate) of Olefin-Based Polymer (A) and Olefin-Based Polymer (B2)) The MFR was measured in accordance with JIS K 7210: 1999. Specifically, the measurement was performed using a "Melt Indexer" manufactured by Toyo Seiki Seisakusho, under conditions of a temperature of 230°C and a load of 2.16 kgf.

[0067] (Solution Viscosity of Styrene-Based Elastomer (B1)) The solution viscosity was measured using a solution obtained by dissolving the styrene-based elastomer (B1) in a toluene solvent to a concentration of 5% by mass, in an atmosphere at a temperature of 30°C, using a Toki Sangyo "B-type viscometer VISCOMETER TVB-10."

[0068] (Average diameter of carbon nanotubes (C)) Carbon nanotubes were observed using a scanning electron microscope (JEOL, JSM-6700M) at an accelerating voltage of 5 kV, and images were taken at 50,000 magnifications (pixel count 1024 × 1280). Next, the short axis length of each of 20 random carbon nanotubes in the taken image was measured, and the number average of the short axis lengths was taken as the average diameter of the carbon nanotubes.

[0069] (Average primary particle size of carbon black (D)) Carbon black was observed using a scanning electron microscope (JSM-6700M, manufactured by JEOL) at an accelerating voltage of 5 kV, and an image was taken at 50,000 times magnification (pixel count 1024 × 1280). Next, the particle size of each of 20 random carbon black particles in the taken image was measured, and the number average value was taken as the average primary particle size of the carbon black.

[0070] The materials used in the examples and comparative examples are as follows. (Olefin elastomer (A)) [Table 1]

[0071] (Styrene-based elastomer (B1)) [Table 2-1]

[0072] (Olefin elastomer (B2)) [Table 2-2]

[0073] (Carbon nanotubes (C)) [Table 3]

[0074] (Carbon Black (D)) [Table 4]

[0075] <Production of Thermoplastic Resin Composition> [Example 1] The olefin-based elastomer (A-1), the styrene-based elastomer (B1-1), the carbon nanotubes (C-1), and the carbon black (D-1) were mixed in the amounts (mass%) shown in Table 5, melt-kneaded, extruded at 230°C using a twin-screw extruder (manufactured by The Japan Steel Works, Ltd.), and granulated to obtain a thermoplastic resin composition.

[0076] [Examples 2 to 22 and Comparative Examples 1 to 8] Thermoplastic resin compositions were obtained in the same manner as in Example 1, except that the materials and blending amounts (mass %) were changed to those shown in Tables 5 to 7, respectively.

[0077] <Evaluation of Thermoplastic Resin Composition> The thermoplastic resin compositions thus obtained were evaluated by the following methods, and the results are shown in Tables 5 to 7.

[0078] [Preparation of molded body] The thermoplastic resin composition was injection molded using an injection molding machine (manufactured by Toshiba Machine Co., Ltd.) with a cylinder setting temperature of 220°C and a mold temperature of 40°C to produce a molded body with a length (injection direction) of 90 mm, a width (direction perpendicular to the injection direction) of 110 mm, and a thickness of 3 mm.

[0079] [Electromagnetic wave absorption performance] FIG. 1 shows the irradiation direction (x), electric field direction (y), and magnetic field direction (z) of the electromagnetic wave when the electromagnetic wave is incident in the thickness direction of the molded body. 1. is a schematic diagram of the measurement of transmission attenuation TL (MD), and 2. is a schematic diagram of the measurement of return attenuation RL (MD). As shown in 1 and 2 of Figure 1, after the obtained molded body was left to stand for one day, the return attenuation RL (MD) and the transmission attenuation TL (MD) were measured in a state where the electric field direction of the electromagnetic wave (y direction in the figure) was parallel to the injection direction (MD direction).

[0080] (Reflection loss RL) As an index of electromagnetic wave absorption performance, the reflection loss (dB) in the millimeter wave frequency band was measured by the following method. A VNA (Vector Network Analyzer) was used as a measuring instrument, an APC-7 (manufactured by Kanto Electronics Application Development Co., Ltd.) was used as a measuring tool, and an E-band antenna (WR-12) was used as an antenna, and the measurement was performed by the free space method. Specifically, the reflection loss was measured for the molded bodies obtained in the examples and comparative examples in an environment of a temperature of 24.8°C and a relative humidity of 48%, in a state in which the injection direction (MD direction) at a measurement frequency of 76.5 GHz and the electric field direction of the electromagnetic wave (y direction in Figure 1) were parallel to each other.

[0081] (Transmission loss TL) As an index of electromagnetic wave absorption performance, the transmission loss (dB) in the millimeter wave frequency band was measured by the following method. A VNA (Vector Network Analyzer) was used as a measuring instrument, an APC-7 (manufactured by Kanto Electronics Application Development Co., Ltd.) was used as a measuring tool, and an E-band antenna (WR-12) was used as an antenna, and the measurement was performed by the free space method. Specifically, the transmission loss was measured for the molded bodies obtained in the examples and comparative examples in an environment of a temperature of 24.8°C and a relative humidity of 48%, in a state in which the injection direction (MD direction) at a measurement frequency of 76.5 GHz and the electric field direction of the electromagnetic wave (y direction in Figure 1) were parallel to each other.

[0082] The electromagnetic wave absorbing performance was evaluated according to the following criteria. ○ (Good): Reflection loss is -5 dB or less and transmission loss is -15 dB or less △(Practical): Reflection loss is -4dB or less and transmission loss is -10dB or less × (Not practical): Reflection loss is greater than -4 dB or transmission loss is greater than -10 dB.

[0083] [Flexibility] As an index of flexibility, Shore D hardness was measured using a Kobunshi Keiki durometer (D type) in accordance with ISO 7619-1:2010. A pusher was brought into contact with a test piece consisting of two overlapping 3 mm thick molded pieces obtained by the above method, and the Shore D hardness (after 5 seconds) was measured by reading the scale after 5 seconds. (Evaluation Criteria) Good: Shore D hardness (after 5 seconds) is less than 40 △ (Practical): Shore D hardness (after 5 seconds) is 40 or more and less than 50 × (Not practical): Shore D hardness (after 5 seconds) is 50 or more

[0084] [Heat resistance] As an indicator of heat resistance, the deflection temperature under load was measured in accordance with ISO 178:2019 using a Yasuda Seiki heat destation tester. The thermoplastic resin composition was injection molded using an injection molding machine (manufactured by Toshiba Machine Co., Ltd.) with a cylinder temperature of 220°C and a mold temperature of 40°C to prepare a multipurpose test piece (thickness 4 mm) according to ISO 10724-1: 1998. The deflection temperature under load was measured using the multipurpose test piece under a load of 0.45 MPa. (Evaluation Criteria) 〇 (Good): Deflection temperature under load is 50℃ or more △ (Practical): Deflection temperature under load is 40℃ or higher, less than 50℃ × (Not practical): Deflection temperature under load is less than 40℃

[0085] [Table 5]

[0086] [Table 6]

[0087] [Table 7]

[0088] From the above evaluation results, it was confirmed that the thermoplastic resin composition of the present invention and the molded article using the same have good electromagnetic wave absorption properties, flexibility, and also excellent heat resistance. In particular, since the composition has excellent reflection loss and transmission loss in the specific frequency band of 60 to 90 GHz called millimeter wave, it can be said that the composition can be suitably used as a molded article for millimeter wave absorber.

Claims

1. A thermoplastic resin composition for an electromagnetic wave absorber, comprising: 50 to 80 mass% of an olefin-based elastomer (A) having a tensile elongation at break of 400 to 700% as measured in accordance with ISO 37:2017; 15 to 35 mass% of an elastomer (B) including at least one selected from the group consisting of a styrene-based elastomer (B1) and an olefin-based elastomer (B2) having a tensile elongation at break of 800% or more as measured in accordance with ISO 37:2017; 0.5 to 5 mass% of carbon nanotubes (C); and 3 to 15 mass% of carbon black (D).

2. The elastomer (B) contains the styrene-based elastomer (B1), The thermoplastic resin composition for an electromagnetic wave absorber according to claim 1, wherein the styrene-based elastomer (B1) comprises at least one selected from the group consisting of a styrene-ethylene-butylene-styrene block copolymer, a styrene-ethylene-propylene block copolymer, a styrene-ethylene-propylene-styrene block copolymer, and a styrene-ethylene-ethylene-propylene-styrene block copolymer.

3. The elastomer (B) contains the styrene-based elastomer (B1), The thermoplastic resin composition for electromagnetic wave absorber according to claim 1, wherein the content of the styrene structure in the styrene-based elastomer (B1) is 15 to 35 mass%.

4. The elastomer (B) contains the olefin-based elastomer (B2), The thermoplastic resin composition for an electromagnetic wave absorber according to claim 1, wherein the olefin-based elastomer (B2) comprises an ethylene-α-olefin copolymer.

5. A molded article obtained by molding the thermoplastic resin composition for electromagnetic wave absorber according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Electromagnetic shielding rubber material

    CN107936343A

  • Polypropylene composition and preparation method thereof

    CN112538219A

  • Conductive resin composition and molded product thereof

    JP2005187811A

  • Conductive resin composition, conductive master batch, molded body, and production method of the same

    JP2016108524A

  • Water heater

    JP2019190758A